Awareness and perception of prevention and management options of sexually transmitted infections among students at secondary school in Rivers State, Nigeria - Florence Mandah; Oluebubechukwu Udi; Pamela Thompsom-Abiye; Basil Ogbu (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction Investments in programs to increase sexual health awareness among young people is ongoing; however, they continue to be exposed to sexually transmitted infections (STIs) and remain vulnerable to risky sexual practices, such as multiple sexual partners and unprotected sexual intercourses, predisposing them to STIs and subsequent treatments from informal and formal health providers. There is limited research on the management practices of young people in Port Harcourt; hence, the study aimed to assess respondents’ awareness and perception of prevention and management options of STIs.